A damage assessment framework for insider threats to national security information: Edward Snowden and the Cambridge Five in comparative historical perspective. Issue 5 (3rd September 2021) - Gioe, David V.; Hatfield, Joseph M.
Abstract: A new 'digital generation' of insider threat has emerged within the US intelligence community. Edward Snowden's mass leaks were not the first transparency-driven digital challenge to the United States Intelligence Community (USIC). Three years before, then U.S. Army Private Bradley Manning provided 500, 000 classified documents to WikiLeaks, which published them to great fanfare for transparency advocates while causing much concern in Washington. These are not isolated cases; the tempo of such mass public disclosures seems to be increasing. In what ways is this new breed of insider threat akin to more traditional counterintelligence breaches such as those of the Cold War? One central point of comparison is the relative damage caused by each, since it would be difficult to sustain the thesis that a new type of insidious threat has emerged if the damage caused by mass leaks was of little consequence when compared to traditional espionage cases. And 'damage' must be evaluated within the social history of the breaches themselves. A systematic approach to the comparison of breaches has remained elusive. This article offers such a framework using the Snowden leak as a case study in contemporary self-tasked digital breaches and the Cambridge Five spy ring as a case study in traditional externally-tasked breaches.